Understanding zoonotic pathogens and risk factors from wildlife in Southeast Asia: a systematic literature review - Ha Thi Thanh Nguyen; Lindahl, Johanna F.; Bett, Bernard K.; Hung Nguyen-Viet; Lam, Steven; Thang Nguyen-Tien; Unger, Fred; Sinh Dang-Xuan; Thanh Xuan Bui; Hien Thanh Le; Lundkvist, Å.; Ling, J.; et al. (Informa UK Limited, 2025)
The COVID-19 pandemic has demonstrated the significance of the human-animal interface in the emergence of zoonotic diseases, with wildlife serving as an important source of infection. A better understanding of the specific pathogens and mechanisms involved is vital to prepare against future outbreaks, especially in Southeast Asia, a hotspot for zoonotic diseases. This paper reviews the published literature on wildlife zoonoses in this region from 2012 to 2022. The results show a diverse range of potential zoonotic pathogens and the widespread occurrence of zoonotic diseases from wildlife. Drivers of zoonotic pathogen spillover include (i) environmental factors (e.g. animal habitat disruption, environmental conditions, exposure to contaminated water/food/soil), (ii) animal factors (e.g. movement patterns, age-related susceptibility), (iii) human factors (e.g. lack of awareness, poor hygiene practices, age, gender and income) and (iv) human-animal-environmental interface factors (e.g. close contact between humans and animals, exposure through visiting animals and presence of vectors). The diverse drivers of zoonoses in Southeast Asia put its communities at risk for infection. To mitigate these risks, global health efforts should consider adopting a One Health approach to foster collaboration across human, animal, and wildlife health sectors. This could involve educating communities on safe animal interactions and improving disease surveillance.